STUDI BAHASA DAN JENDER: SEJARAH SINGKAT, ANCANGAN, DAN MODEL ANALISIS - Katubi, Katubi (P2KK LIPI, 2004)
Today’s speakers inherit the idea that language is a weapon, used by the inception of the Women’s Liberation movement, many researchers and writers have discussed language and gender. But why should language, and knowledge about language, be a resource for the powerfull alone? Feminists have constanly asked this question, addressing it in various ways. Here the writer not only would like to explain briefly the history of language and gender studies, but also the approaches and models of analysis to that studies.